A comparative study of endoscopic and microscopic myringoplasty in a rural tertiary care teaching hospital - Kavathur, Viswanathan; Anchery, Vineeth Abraham (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Myringoplasty is the procedure done to repair the tympanic membrane perforation. In this study we aimed to compare the results of endoscopic myringoplasty and microscopic tympanoplasty. Methods: A total of 50 patients with central perforation of tympanic membrane and dry ear of minimum 6 months were divided into two groups of 25 each. The even serial numbers were subjected to microscopic myringoplasty through post aural route and odd serial numbers were subjected to endoscopic myringoplasty done through endomeatal route. Both the procedures were done under general anaesthesia. Dried temporalis fascia graft was used and follow up till 1 year post op. Air-bone gap closure, average time taken for surgery, success and failure rates, scar evaluation by doctor and patient along with postoperative return to routine activity were compared. The p value was calculated to find out statistical significance. Results: Post operatively the average air-bone gap reduced to 12.6 dB in endoscopic group and 14.28 dB in microscopic group. There was no statistical significant difference in the time taken for both the procedures. There was significant difference in the assessment of postoperative scar and number of days taken for return to routine activity. The success and failure rates of both the procedures were also found to be comparable. Conclusions: Our study showed that the success rates and average time taken for the procedures were the same for both the techniques but a better cosmetic appeal and considerably fewer days for return to routine activity by the patients who underwent endoscopic procedure.